Construction of Social Reality In The Badui Society Regarding The Covid 19 Pandemic - Ika Yuliasari; Made Wilantara; Novianty Elizabeth Ayuna (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
DKI Jakarta, West Java, and Banten are the provinces that were the epicenter of covid 19. Every individual at that time had the potential to be exposed. However, the Badui community that also lived in the epicenter field was not much exposed. The purpose of this study was to determine the construction of social reality in the Badui society against zero percent COVID-19 transmission. The research approach is qualitative with a constructivist paradigm. The research method is descriptive with purposive data collection. The results showed that stakeholders perform effective management of externalization-internalization communication, namely instructions from the central government can be implemented with maximum coordination. The chieftain carried out communication management to legitimize socialization, namely emphasizing that COVID-19 must be overcome by treating the ancestral heritage and following the interacting instructions issued by the government. Communication management institutionalization of objectification is performed, namely, the community must obey the rules and traditional culture and believe in the Almighty. The leaders of the outer Badui conduct socialization of Communication Management, which provides input and warnings to the local community to maintain the health of their respective families.